Revitalisasi Ibadah dalam Mengatasi Tantangan Majelis yang Mengabaikan Pelayanan di Jemaat Imanuel Natoen - Harun Y. Natonis; Yepri Leluk; Taroci Cantika Nafi; Irene Bire Logo (Jurnal Ilmiah Literasi Indonesia, 2026)
Jemaat Immanuel Natoen faces serious challenges due to church councils neglecting core service duties, resulting in spiritual stagnation and declining congregational participation. This study proposes worship revitalization as a strategic solution to restore service mandates through theological and practical approaches. Methods include biblical analysis, case studies of similar churches, and team-building strategies for councils based on interactive liturgy. Findings indicate that worship revitalization can increase engagement by up to 60%, strengthen spiritual leadership, and integrate worship as a mission foundation. Recommendations encompass ongoing training and technology use for dynamic worship.”